Look at Mummy: challenges in training parents to deliver a home treatment program for childhood apraxia of speech in a rural Canadian community - Jacqueline Lim; Patricia McCabe; Alison Purcell (James Cook University, 2020)
Introduction: Children requiring speech pathology services in rural and remote locations face many barriers in accessing adequate services. This has particular consequences for children who need intensive treatment for therapy to be effective, such those with childhood apraxia of speech (CAS). Parent training has been used to overcome speech pathology service delivery barriers for a range of other communication disorders. However, the effectiveness of training parents to deliver a motor-based treatment for CAS within rural and remote contexts has not been evaluated. This study examined the effectiveness and feasibility of training parents in a rural community to use the treatment approach of dynamic temporal and tactile cueing (DTTC) in order to provide more intensive treatment sessions at home. Methods: The study used an experimental single case across behaviours design and parent interviews to evaluate outcomes both quantitatively and qualitatively. The study included four parent-child dyads from a mixed socioeconomic rural community in Canada. Child participants ranged in age from 3 years to 8 years. Child treatment outcomes were measured using an improvement rate difference (IRD) calculation based on percentage of phonemes correct. Fidelity to the treatment protocol was measured using a fidelity score. Results: All parents reported challenges in carrying out the program due to social and behavioural challenges. Parents also reported benefits such as being able to spend more time with their child and learning some useful cueing techniques. Only one of the four participants had a moderate effect size for his target words (IRD=57%). Conclusion: While training parents to deliver DTTC may be effective for some parent-child dyads, clinicians are advised that parent training may not be suitable for all families, and parents in rural and remote communities may face particular social circumstances that make following through with an intensive treatment program difficult.